ANALISIS PENGALAMAN BELAJAR ON THE JOB TRAINING PADA PRAKTIK KERJA INDUSTRI DI HOUSEKEEPING DEPARTMENT - Aditya, Irvan; Yani Achdiani; Neni Rohaeni (Jurnal Pendidikan dan Perhotelan (JPP), 2025)
The learning experience of industrial work practice often varies due to differences in educational backgrounds and the approaches implemented in each school. To align work perceptions in the Housekeeping Department, an on-the-job training program was designed as an effort to provide a uniform learning experience. This research aims to analyze the learning experiences for industrial work practices after participating in the on-the-job training program with various aspects provided in the Housekeeping Department. The research uses a quantitative method with a descriptive design. This descriptive research is intended to provide a clear picture of the learning experiences from on-the-job training in industrial work practices in the Housekeeping Department. Data were collected through interviews and questionnaires distributed to industrial practice students in the Housekeeping Department. The sample in this study consists of 37 industrial internship students in the Housekeeping Department of Hotel Grand Tjokro Premiere Bandung. The research results show that on-the-job training in the Housekeeping Department provides a comprehensive learning experience, encompassing mastery of theory, development of practical skills, and formation of a professional attitude. Based on the research findings, several aspects were identified as key in shaping a learning experience that aligns with the working conditions in the field. This program has proven effective in preparing students to face the challenges of the workforce in the hospitality industry by providing relevant knowledge, applicable skills, and a professional work attitude.